Accident Prevention and Traffic Safety for Sekolah Alam Robbani Bekasi - (KidSafe) - Hermanto Dwiatmoko; Muhammad Isradi; Joewono Prasetijo; Munzilah MD Rohani; Syafiadi Rizki Abdila; Andri Irfan Rifai (Communautaire: Journal of Community Service, 2023)
In 2020, the number of traffic accidents from student age was 42,604 people. Meanwhile, there were 26,355 traffic accidents from student age until September this year. Based on gender, the majority of traffic accidents occurred in men. Traffic accidents contribute greatly as one of the causes of death in Indonesia.  Traffic accidents have a high fatality rate.  Data shows that in one year, 25, 2666 people died due to traffic accidents.  Among the victims of traffic accidents are school children. About 95% of the causes of accidents are human error factors. The purpose of this community service is to provide an understanding of good traffic in early childhood. Understanding facilities for pedestrians and cycling lanes. The method provided is by providing material, pictures of traffic signs, and play displays related to traffic signs. Evaluation and results of activities by dividing students into several small groups and this is effective, students are able to explain traffic signs, and good traffic procedures, especially for users of pedestrian facilities and safe cyclist routes.